Characterization of quorum-sensing and virulence factors associated genes among uropathogenic Enterococcus faecalis - Dina Ashraf; Mona Shaaban; Ramadan Hassan; Abeer Abd El-Aziz (Microbes and Infectious Diseases)
Background: Enterococcus faecalis (E. faecalis) is a significant concern in healthcare due to its ability to cause serious infections and increasing antibiotic resistance, commonly causes urinary tract infections (UTIs) and possesses various virulence factors. The study aimed to assess the antimicrobial sensitivity of E. faecalis isolates from UTIs, as well as investigate the presence of fsr quorum sensing (QS) and virulence-related genes. Additionally, the correlation between antimicrobial susceptibility and the presence of QS and virulence genes was examined. Methods: Thirty-seven uropathogenic E. faecalis isolates were tested for susceptibility to ten antibiotics using Kirby-Bauer disk diffusion. Then PCR was conducted to detect the presence of fsr QS and virulence associated genes. The correlation between QS genes, virulence genes and antimicrobial sensitivity was analyzed. Results: Resistance rates were high for ampicillin (100%), kanamycin (94.5%), ciprofloxacin (86.5%), levofloxacin (83.8%), erythromycin (83.8%), and tetracycline (78.4%). Approximately half of the isolates were resistant to chloramphenicol (48.6%) and amoxicillin-clavulanate (43.3%). Nitrofurantoin (10.8%) and vancomycin (8.10%) had the lowest resistance rates. PCR analysis detected fsrB and fsrC genes in 81% and 83.7% of isolates, respectively. The gelE and sprE genes were present in 72.9% and 89% of isolates, respectively. The efaA gene was amplified in all isolates, while the esp, ebpA, and asa1 genes were prevalent in 91.8%, 83.7%, and 64.8% of isolates, respectively. The cylLL gene was found in 48.6% of isolates. Conclusion: These findings emphasize the concerning issue of antimicrobial resistance and the presence of virulence factors in multi-virulent E. faecalis isolates from UTIsز